Anti-Aging β-Klotho Gene-Activated Scaffold Promotes Rejuvenative Wound Healing Response in Human Adipose-Derived Stem Cells - Ashang L. Laiva (MDPI AG, 2021)
Wound healing requires a tight orchestration of complex cellular events. Disruption in the cell-signaling events can severely impair healing. The application of biomaterial scaffolds has shown healing potential; however, the potential is insufficient for optimal wound maturation. This study explored the functional impact of a collagen-chondroitin sulfate scaffold functionalized with nanoparticles carrying an anti-aging gene β-Klotho on human adipose-derived stem cells (ADSCs) for rejuvenative healing applications. We studied the response in the ADSCs in three phases: (1) transcriptional activities of pluripotency factors (Oct-4, Nanog and Sox-2), proliferation marker (Ki-67), wound healing regulators (TGF-β3 and TGF-β1); (2) paracrine bioactivity of the secretome generated by the ADSCs; and (3) regeneration of basement membrane (fibronectin, laminin, and collagen IV proteins) and expression of scar-associated proteins (α-SMA and elastin proteins) towards maturation. Overall, we found that the β-Klotho gene-activated scaffold offers controlled activation of ADSCs’ regenerative abilities. On day 3, the ADSCs on the gene-activated scaffold showed enhanced (2.5-fold) activation of transcription factor Oct-4 that was regulated transiently. This response was accompanied by a 3.6-fold increase in the expression of the anti-fibrotic gene TGF-β3. Through paracrine signaling, the ADSCs-laden gene-activated scaffold also controlled human endothelial angiogenesis and pro-fibrotic response in dermal fibroblasts. Towards maturation, the ADSCs-laden gene-activated scaffold further showed an enhanced regeneration of the basement membrane through increases in laminin (2.1-fold) and collagen IV (8.8-fold) deposition. The ADSCs also expressed 2-fold lower amounts of the scar-associated α-SMA protein with improved qualitative elastin matrix deposition. Collectively, we determined that the β-Klotho gene-activated scaffold possesses tremendous potential for wound healing and could advance stem cell-based therapy for rejuvenative healing applications.